Impact of foliar application of syringic acid on tomato (Solanum lycopersicum L.) under heavy metal stress-insights into nutrient uptake, redox homeostasis, oxidative stress, and antioxidant defense - Ma, Jing; Saleem, Muhammad Hamzah; Ali, Baber; Rasheed, Rizwan; Ashraf, Muhammad Arslan; Aziz, Humera; Ercisli, Sezai; Riaz, Sana; Elsharkawy, Mohsen Mohamed; Hussain, Iqbal; Alhag, Sadeq K.; Ahmed, Ahmed Ezzat; et al. (Frontiers in Plant Science, 2022)
Soil contamination with toxic heavy metals [such as lead (Pb)] is becoming a serious global problem due to the rapid development of the social economy. However, accumulation of Pb in plant parts is very toxic for plant growth and decreases crop yield and productivity. In the present study, we have investigated the different concentrations of Pb in the soil i.e., [0 (no Pb), 50, and 100 mg kg–1] to study plant growth and biomass, photosynthetic pigments and gas exchange characteristics, oxidative stress indicators and the response of various antioxidants (enzymatic and non-enzymatic), nutritional status of the plant, organic acid exudation pattern and also Pb accumulation in the roots and shoots of the plants of two varieties of tomato (Solanum lycopersicum L.) i.e., Roma and Cchuas, grown under different levels of synergic acid [no spray (NS), water spray (WS), 0.3-0.5°μM]. Results from the present study showed that the increasing levels of Pb in the soil decreased non-significantly (P < 0.05) shoot length, root length, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, chlorophyll-a, chlorophyll-b, total chlorophyll, carotenoid content, net photosynthesis, stomatal conductance, transpiration rate, soluble sugar, reducing sugar, non-reducing sugar contents, calcium (Ca2+), magnesium (Mg2+), iron (Fe2+), and phosphorus (P) contents in the roots and shoots of the plants. However, Pb toxicity also induced oxidative stress in the roots and shoots of the plants by increasing malondialdehyde (MDA), hydrogen peroxide (H2O2), and electrolyte leakage (EL) which also induced increased the compounds of various enzymatic and non-enzymatic antioxidants and also organic acids exudation pattern in the roots such as fumaric acid, acetic acid, citric acid, formic acid, malic acid, oxalic acid contents and increased the concentration of Pb in different parts of the plants. Results also show that the Cchuas showed better growth and development compared to Roma, under the same levels of Pb in the soil. The alleviation of Pb toxicity was induced by the application of synergic acid, and results showed that the application of synergic acid increased plant growth and biomass and also increased the gas exchange characteristics and antioxidant capacity in the roots and shoots of the plants. Research findings, therefore, suggested that synergic acid application can ameliorate Pb toxicity in S. lycopersicum varieties and result in improved plant growth and composition under metal stress as depicted by balanced exudation of organic acids.